2019
DOI: 10.3892/etm.2019.8022
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of miR‑4492 and IL‑10 is involved in chronic rhinosinusitis with nasal polyps

Abstract: Chronic rhinosinusitis (CRS) is one of the most common types of respiratory disease and affects a large proportion of the population worldwide. The clinical differences between CRS with nasal polyps (CRSwNP) and CRS without nasal polyps (CRSsNP) facilitate studies on the development of polyps. In the present study, next-generation sequencing was performed to identify differentially expressed microRNAs (miRNAs/miRs) in CRSwNP vs. CRSsNP tissues and subsequently validated the expression of selected genes using r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 56 publications
3
12
0
Order By: Relevance
“…Studies performed on CRSwNP mainly focus on exploring potential inflammatory factors and targeted therapy [ 17 , 18 ]. Moreover, a previous study showed that miR-4492/IL-10 interaction played a crucial role in CRSwNP [ 19 ]. Xiao et al discovered that IL-21 was highly expressed in CRSwNP groups, and suggested that IL-21 might be a therapeutic target for CRSsNP therapy [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies performed on CRSwNP mainly focus on exploring potential inflammatory factors and targeted therapy [ 17 , 18 ]. Moreover, a previous study showed that miR-4492/IL-10 interaction played a crucial role in CRSwNP [ 19 ]. Xiao et al discovered that IL-21 was highly expressed in CRSwNP groups, and suggested that IL-21 might be a therapeutic target for CRSsNP therapy [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the presence or absence of polyposis, CRS can be divided into CRSwNP and CRSsNP ( 5 ). Though the occurrence of CRSwNP is infrequent, medical intervention is unsuccessful for a large proportion of patients with CRSwNP ( 8 ). In addition to inflammation, CRSwNP and CRSsNP are characterized by remodeling of structural components, particularly in the epithelium ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…CRSwNP is more closely associated with obstruction of the nasal cavity and anosmia ( 7 ). Clinically, CRSwNP is frequently resistant to medical therapy ( 8 ). Recently, it has been demonstrated that epithelial-to-mesenchymal transition (EMT) and its effects on nasal epithelial cells may result in the tissue remodeling of nasal polyps ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MicroRNAs (miR) are a class of small noncoding RNAs that regulate the expression of target genes by preventing the translation of target mRNAs or inducing their degradation, or both, depending on the level of complementarity (12). MicroRNAs are involved in the regulation of immune systems and inflammation (13,14), and increasing studies show that miRNAs play an important role in the pathogenesis of NP (15)(16)(17)(18). MiR-21, a member of microRNAs, is highlighted as potentially playing a pivotal role in regulating inflammation (19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%